ALTERNATIVE SOLUTION TO OVERCOME THE CORROSION OF CRROSIVE ENVIRONMENT STRUCTURES - Prabowo Setiyawan (International Conference on Coastal and Delta Areas, 2015)
This paper aims to understand the cost-effective methods of corrosion problems solutions of structures constructed at corrosive areas. The solution is basically done by providing additional layer on the steel or concrete structural components. The study was done by reviewing the existing design standards and the research results conducted by the previous researchers as well as the publications issued by the company concerning on the corrosion problems solutions. It can be concluded that the corrosion problems decreasing the structural strength as well as life of the structure can be caused by chloride/carbonation, contact with water (moisture) and contact with oxygen. It can also be inferred that regarding to the purpose the corrosion problems solutions could be classified as corrosion protection, types of application and longevity. In addition, the chosen method and the product used to overcome the corrosion problems of the structures are affected and should be considered the local environment especially related to the chloride concentration, concrete properties, humidity and temperature.Keywords: steel structure, concrete structure, corrosive environments, corrosion problems solutions